Persistent COVID-19 Infection In A B-Cell Depleted Patient With Successful Viral Clearance After Tixagevimab-Cilgavimab - Li, Qi; Zerrouki, Karima; Point, Floriane; Lapierre, Simon Grandjean; Durand, Madeleine (Archives of Clinical and Medical Case Reports, 2024)
Background: Patients receiving B-cell depleting regimens are at increased risk of persistent COVID-19. Selecting effective treatments for these patients becomes challenging with new viral mutations conferring resistance to available targeted therapies. Case presentation: We describe a case of persistent COVID-19 in a patient under rituximab for ANCA-associated vasculitis. She obtained a first positive PCR test in April 2022. Over the following 115 days, she was hospitalized twice for worsening fever and respiratory symptoms which resolved transiently with remdesivir. PCR tests were positive for the Omicron BA.2 variant of SARS-CoV-2 throughout the two hospitalizations. Viral persistence rather than re-infection was confirmed using viral genomic sequencing. The patient received tixagevimabcilgavimab at the end of her second hospitalization, and subsequently obtained negative PCR results. Conclusion: Persistent COVID-19 should be rapidly suspected in immunocompromised individuals with symptom recurrence following recent COVID-19 infection. Anti-SARS-CoV-2 monoclonal antibodies may be a potentially effective treatment of persistent infections in this patient population.